Problems of the implementation of economic rights of internally displaced persons - Глібко, С. В.; Розгон, О. В.; Подрез-Ряполова, І. В. (НДІ ПЗІР НАПрН України, 2022)
In the conditions of martial law on the territory of Ukraine there is a need to develop an effective mechanism for exercising the rights of internally displaced persons. The problems of exercising economic rights, in particular, the problems in the field of realization of property rights by internally displaced persons, become especially relevant. The purpose of this article is to analyze research and the main provisions of regulations and draft laws relating to the implementation of economic rights of internally displaced persons. The study of the works of scientists allowed establishing and assessing the state of research of the chosen topic, to identify and investigate the problematic issues that have arisen at the present stage and to identify ways to solve them. In particular, the general problems of protection of the rights of internally displaced persons were outlined, which are the problems of realization of the rights of internally displaced persons of institutionalorganizational, legal and socio-economic nature. Within the framework of this study the analysis of the state of normative regulation of legal relations on the chosen subject of the following main periods was carried out: before the imposition of martial law on the territory of Ukraine and the period related to the armed aggression of the Russian Federation against Ukraine’s sovereignty. It is noted that in the period before the imposition of martial law in Ukraine, the national concept of protection and restoration of property rights of internally displaced persons and internally displaced persons has not been effectively applied. The provisions of the draft Law of Ukraine «On the Principles of State Policy in Transition» of August 9, 2021 are considered. It is proved that for effective legal regulation of problematic issues that may arise in the transition period, it is necessary to timely develop relevant legislation (regulations) that can solve the problems of legal protection of citizens of Ukraine and legal entities of Ukraine, rights and legitimate interests whose property rights have been violated as a result of the armed aggression of the Russian Federation and the temporary occupation of the territory of Ukraine. The existence of problems with the implementation of the Law of Ukraine «On Ensuring the Rights and Freedoms of Internally Displaced Persons» in the field of protection of property rights was identified; their importance and relevance were emphasized. It is established that the legislation of Ukraine in the field of legal regulation of property relations with the participation of internally displaced persons needs to be improved and appropriate changes made that will provide protection and additional guarantees for the exercise of property rights. In particular, they stressed the need to develop a mechanism to restore property rights, create a single database of property of internally displaced persons and adopt a special legal act governing guarantees of compensation for destruction (damage) of property due to hostilities, terrorist acts, sabotage caused by the military aggression of the Russian Federation. In addition, the need to stimulate the realization of entrepreneurial and innovative potential and further comprehensive scientific and legal research to create optimal conditions and increase the efficiency of entrepreneurial and innovative activities was emphasized. // В умовах воєнного стану на території України виникає необхідність розроблення дієвого механізму реалізації прав внутрішньо переміщених осіб. Особливої актуальності набувають проблеми здійснення економічних прав, зокрема, проблеми у сфері реалізації внутрішньо переміщеними особами майнових прав. Метою цієї статті є аналіз наукових досліджень та основних положень нормативно- правових актів та проєктів законів, які стосуються сфери реалізації економічних прав внутрішньо переміщених осіб. Вивчення праць науковців дозволило встановити й оцінити стан дослідження обраної теми, виявити та дослідити проблемні питання, що постали на сучасному етапі та визначити шляхи їх вирішення. Зокрема, були окреслені загальні проблеми щодо захисту прав внутрішньо переміщених осіб, якими є проблеми реалізації прав вимушених переселенців інституційно-організаційного, правового та соціально- економічного характеру. В рамках цього дослідження проведений аналіз стану нормативного регулювання правовідносин з обраної тематики наступних основних періодів: до введення воєнного стану на території України та періоду, пов›язаного зі збройною агресією Російської Федерації проти суверенітету України, введенням воєнного стану в Україні і тимчасовою окупацією частини території України. Відмічено, що у період до введення воєнного стану в Україні не набула ефективного застосування загальнодержавна концепція захисту і відновлення майнових прав внутрішньо переміщених осіб та вимушених переселенців. Розглянуті положення проєкту Закону України «Про засади державної політики перехідного періоду» від 09 серпня 2021 року. Доведено, що для ефективного правового регулювання проблемних питань, які можуть виникнути у перехідний період, необхідна своєчасна розробка відповідних законодавчих норм (положень), які зможуть розв’язати проблеми правового захисту громадян України і юридичних осіб України, права і законні інтереси на об’єкти права власності яких порушені внаслідок збройної агресії Російської Федерації та тимчасової окупації території України. Визначено наявність проблем щодо реалізації норм Закону України «Про забезпечення прав і свобод внутрішньо переміщених осіб» у сфері захисту права власності, наголошена їх важливість та актуальність. Встановлено, що законодавство України у сфері правового регулювання відносин власності за участю внутрішньо переміщених осіб потребує вдосконалення та внесення відповідних змін, які забезпечать захист та додаткові гарантії здійснення права власності. Зокрема, наголошено на необхідності розробки механізму відновлення права власності, створення єдиної бази обліку майна внутрішньо переміщених осіб та прийняття спеціального нормативного-правового акту, що регулює питання надання гарантій компенсації руйнування (пошкодження) майна громадян внаслідок бойових дій, терористичних актів, диверсій, спричинених військовою агресією Російської Федерації. Крім того, наголошено на необхідності стимулювання реалізації підприємницького та інноваційного потенціалу та подальших комплексних науково-правових досліджень щодо створення оптимальних умов та підвищення ефективності провадження підприємницької та інноваційної діяльності.
Проблеми реалізації економічних прав внутрішньо переміщених осіб
Keywords: internally displaced person; economic rights; martial law; occupied territories; property rights; внутрішньо переміщена особа; воєнний стан; економічні права; окуповані території; право власності